How can micelle systems be rebuilt by a heating process? - da Silva-Filho, Miguel Adelino; Vieira da Silva Siqueira, Scheyla Daniela; Freire, Larissa Bandeira; de Araujo, Ivonete Batista; Gyselle de Holanda e Silva, Kattya; Medeiros, Aldo da Cunha; Araujo-Filho, Irami; Oliveira, Anselmo Gomes de [UNESP]; Tabosa do Egito, Eryvaldo Socrates (Dove Medical Press Ltd, 2012)
The aim of this work was to evaluate how an aqueous micellar system - containing Amphotericin B (AmB) and sodium deoxycholate (DOC) can be rebuilt after heating treatment. Also, a review of the literature on the physicochemical and biological properties of this new system was conducted. Heated (AmB-DOC-H) and unheated (AmB-DOC) micelles were then diluted at four different concentrations (50 mg.L-1, 5 mg.L-1, 0.5 mg.L-1, and 0.05 mg.L-1) to perform physicochemical studies and a pharmacotoxicity assay, in which two cell models were used for the in vitro experiments: red blood cells (RBC) from human donors and Candida parapsilosis (Cp). While potassium (K+) and hemoglobin leakage from RBC were the parameters used to evaluate acute and chronic toxicity, respectively, the efficacy of AmB-DOC and AmB-DOC-H were assessed by K+ leakage and cell survival rate from Cp. The spectral study revealed a slight change in the AmB-DOC aggregate peak from 327 nm to 323 nm, which is the peak for AmB-DOC-H. Although AmB-DOC and AmB-DOC-H exhibited different behavior for hemoglobin leakage, AmB-DOC produced higher leakage than AmB-DOC-H at high concentrations (from 5 mg.L-1). For K+ leakage, both AmB-DOC and AmB-DOC-H showed a similar profile for both cell models, RBC and Cp (P < 0.05). AmB-DOC-H and AmB-DOC also revealed a similar profile of activity against Cp with an equivalent survival rate. In short, AmB-DOC-H showed much less toxicity than AmB-DOC, but remained as active as AmB-DOC against fungal cells. The results highlight the importance of this new procedure as a simple, inexpensive, and safe way to produce a new kind of micelle system for the treatment of systemic fungal infections.
Keywords: micelles; nanotechnology; pre-heated amphotericin B; super-aggregates